2016
DOI: 10.1038/srep37905
|View full text |Cite
|
Sign up to set email alerts
|

Four translation initiation pathways employed by the leaderless mRNA in eukaryotes

Abstract: mRNAs lacking 5′ untranslated regions (leaderless mRNAs) are molecular relics of an ancient translation initiation pathway. Nevertheless, they still represent a significant portion of transcriptome in some taxons, including a number of eukaryotic species. In bacteria and archaea, the leaderless mRNAs can bind non-dissociated 70 S ribosomes and initiate translation without protein initiation factors involved. Here we use the Fleeting mRNA Transfection technique (FLERT) to show that translation of a leaderless r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 60 publications
(118 reference statements)
1
42
0
1
Order By: Relevance
“…Phosphorylation of the α subunit of the eIF2 complex inhibits eIF2B-mediated exchange of eIF2•GDP to eIF2•GTP [66,72,73], thus reducing the formation of the active TC [63,64]. However, translation of a subset of cellular and viral mRNAs appeared to be resistant to eIF2α phosphorylation, despite requiring Met-tRNA i [3,[48][49][50][51][52][53][54][55][56][57][58]. These mRNAs in many instances do not require m 7 G cap recognition by eIF4E, and their translation may rely on alternative initiation mechanisms such as internal initiation and/or re-initiation [3,[50][51][52][53].…”
Section: Eukaryotic Initiation Factor 2 (Eif2)mentioning
confidence: 99%
See 2 more Smart Citations
“…Phosphorylation of the α subunit of the eIF2 complex inhibits eIF2B-mediated exchange of eIF2•GDP to eIF2•GTP [66,72,73], thus reducing the formation of the active TC [63,64]. However, translation of a subset of cellular and viral mRNAs appeared to be resistant to eIF2α phosphorylation, despite requiring Met-tRNA i [3,[48][49][50][51][52][53][54][55][56][57][58]. These mRNAs in many instances do not require m 7 G cap recognition by eIF4E, and their translation may rely on alternative initiation mechanisms such as internal initiation and/or re-initiation [3,[50][51][52][53].…”
Section: Eukaryotic Initiation Factor 2 (Eif2)mentioning
confidence: 99%
“…However, translation of a subset of cellular and viral mRNAs appeared to be resistant to eIF2α phosphorylation, despite requiring Met-tRNA i [3,[48][49][50][51][52][53][54][55][56][57][58]. These mRNAs in many instances do not require m 7 G cap recognition by eIF4E, and their translation may rely on alternative initiation mechanisms such as internal initiation and/or re-initiation [3,[50][51][52][53]. It was found that a subset of factors, i.e., Ligatin/eIF2D [59,60], the oncogene MCT-1 and DENR (together) [59] as well as eIF5B (alone) [49,74,75] can promote efficient recruitment of Met-tRNA i to 40S/mRNA complexes under conditions of inhibition of eIF2 activity, or its absence.…”
Section: Eukaryotic Initiation Factor 2 (Eif2)mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, translation of an mRNA with a very short leader (5 nt) revealed the weakest acceleration effect. This suggests, in the context of the cyclic reinitiation model, that the distance between the cyclization point (cap) and AUG can be too small for CLAR to occur efficiently while still being enough for the efficient de novo cap-dependent initiation (Figure 4b, see also [51]).…”
Section: Acceleration Rate Depends On the Length Of 5' And 3 Utrsmentioning
confidence: 99%
“…15), of the simulated fluorescence intensities, and from G(τ ) we estimate the time 250 lag, τ F CS , at which correlations disappear (see Fig 1C and Methods). In the ROA 251 approach, we simulate the addition of a chemical compound, such as Harringtonine, 252 which binds the 60S ribosome subunit and prevents ribosome assembly [26], and we 253 record the average time, τ ROA , at which protein fluorescence disappears from the RNA 254 (see Fig 1D and Methods). To approximate variability in the specific time at which the 255 drug reaches the mRNA and blocks ribosome initiation, we assume that the time of 256 initiation blockage occurs at a normally distributed time of 60 ± 10 seconds [27].…”
mentioning
confidence: 99%